SOSIALISASI DIGITALISASI MEDIA BELAJAR BAGI TENAGA PENDIDIK SEBAGAI UPAYA MENINGKATKAN LITERASI DAN NUMERASI PESERTA DIDIK - Pertiwi, Novia Ayu Sekar (Jurnal Pengabdian Siliwangi, 2024)
An educator is expected to be able to use learning media in the teaching process, both simple media and technology-based media. However, in reality there are still some teachers who teach only using lectures and blackboards as learning media. Based on the results of interviews with educators in Dukuhdimoro village, there are problems that need attention, namely the lack of use of digital technology in the learning process and educators not being familiar with applications that support the digitalization of learning media. The problems identified above are then socialized between the work program team and partner educators in various agencies with the aim of helping educators in various agencies utilize technology in the learning process and helping educators become familiar with applications that support the digitalization of learning media. In this Community Partnership Program scheme, community service activities are carried out using the Service Learning (SL) method. In the socialization activity on the digitalization of learning media to educators, lecture methods and question and answer discussions are used to provide an understanding of what is meant by "Digitalization of Learning Media". This socialization activity is expected to solve the problems faced by educators in Dukuhdimoro village. The following Table 1 shows the solution as a solution to existing problem formulations. Based on the results of community service, it can be concluded that this socialization activity is to encourage educators to utilize and integrate technological advances in learning media, so that guidance and direction from resource persons is carried out continuously by establishing cooperation between the various parties involved. in the world of education and using available applications to create innovative and creative learning media, which can increase the effectiveness of learning.Keywords: Digitalization, Media, Learning, Educators